2017
DOI: 10.1155/2017/1672567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Orange Juice Consumption on Body Composition and Nutritional Status in Overweight/Obese Female: A Pilot Study

Abstract: The main objective of this research was to determine whether a commercial orange juice rich in anthocyanins could have an effect on body weight and on clinical parameters related to obesity including antioxidant status, lipid profile, and metabolic and inflammatory biomarkers. 11 women with an average BMI of 34.4 ± 4.8 kg/m2 were enrolled in a pilot study. Over a period of 12 weeks they received 500 mL daily dose into two doses (250 mL) of commercial red orange juice (COJ). The biochemical parameters were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
1
43
0
1
Order By: Relevance
“…Detailed results can be found in Supplementary Material. There is currently a growing scientific interest in nutraceuticals because of their potential effects on the treatment of obesity and being overweight [16]. In the present study, we observed that CitrusiM ® could increase lean body mass, and reduce fat mass.…”
Section: Resultssupporting
confidence: 57%
“…Detailed results can be found in Supplementary Material. There is currently a growing scientific interest in nutraceuticals because of their potential effects on the treatment of obesity and being overweight [16]. In the present study, we observed that CitrusiM ® could increase lean body mass, and reduce fat mass.…”
Section: Resultssupporting
confidence: 57%
“…Evidence suggests that diets composed of plant-rich foods high in bioactive compounds, such as flavonoids, have a protective role for type 2 diabetes mellitus (DM) (4) and obesity (5). Flavonoids belong to the group of polyphenols and are classified into six subclasses: flavan-3-ols, anthocyanidins, flavonols, flavanones, flavones and isoflavones (6).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, daily intake of 500 mL of commercially available red orange juice (COJ) for 12 weeks resulted in no significant reduction of body weight or plasma inflammatory markers; however, a lowering of total and low density lipoprotein (LDL) cholesterol in obese women was reported with COJ . These negative effects may be due to higher sugar content in COJ compared to fresh orange juice.…”
Section: Adipose Tissue Inflammation and Obesitymentioning
confidence: 99%